Composite bone repair material, preparation method and application

By preparing porous silk protein/gelatin composite materials, the problem of insufficient porous structure and biological activity in the prior art was solved, and the cell adhesion, proliferation and migration were improved, and the osteogenic activity and mechanical properties of bone repair materials were enhanced.

CN120361312APending Publication Date: 2025-07-25SHANGHAI REGE-INNOVATION MEDICAL TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510521561.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-06
Filing Date
2025-04-24
Publication Date
2025-07-25

AI Technical Summary

Technical Problem

The existing composite materials do not have a porous structure, resulting in inefficient adhesion, proliferation and migration of bone repair cells. The silk protein scaffold material does not contain gelatin components and has weak biological activity.

Method used

The silk protein solution obtained by degumming the mulberry silkworm cocoon with the gelatin solution and crosslinking with horseradish peroxidase, hydrogen peroxide and glutamine transaminase to form silk protein/gelatin gel blocks, and then treated with ammonium sulfate solution and freeze-dried to prepare porous silk protein/gelatin composite material.

Benefits of technology

The prepared composite material has a porous structure, which improves cell adhesion, proliferation and migration capabilities, enhances osteogenic activity, and has good biocompatibility and mechanical properties. It is suitable for filling and regeneration and repair of bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120361312A_ABST
    Figure CN120361312A_ABST
Patent Text Reader

Abstract

The invention relates to a composite bone repair material, a preparation method and application, the preparation method comprises the following steps: immersing silkworm cocoons in a soap salt solution for degumming, drying to prepare degummed silk, dissolving the degummed silk in a lithium bromide solution, dialyzing for desalting, and concentrating to obtain a regenerated silk protein solution; mixing the regenerated silk fibroin solution with a gelatin solution to obtain a gel solution; mechanically shaking the gel solution, so that the gel solution is uniformly mixed, uniformly distributed bubbles are formed in the gel solution, and a silk protein / gelatin gel block is obtained; soaking and cleaning the silk protein / gelatin gel block in an ammonium sulfate solution to obtain silk protein / gelatin cross-linked gel; and freeze-drying the fibroin / gelatin cross-linked gel to obtain the fibroin / gelatin composite material. The composite bone repair material has the advantages that the composite bone repair material has a bionic porous structure, has excellent mechanical properties and also has good biocompatibility and osteogenic activity. The material can be applied to filling and regeneration repair of skull defects of the orthopedics department, the oral cavity, the plastic surgery (maxillofacial) and the neurosurgery department, and has high industrial production and clinical application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical materials, and in particular to a composite bone repair material, a preparation method and an application thereof. Background Art

[0002] Silk fibroin, as a natural biological protein material, has the advantages of good biocompatibility, easy availability, good swelling and natural antibacterial properties. Foreign literature has reported the application of silk fibroin to make bone tissue repair materials, such as scaffolds, gels and fiber meshes, and animal experiments have confirmed its good biocompatibility. However, due to the slow degradation rate of pure silk protein materials and the lack of bioactive peptides compared with other proteins such as collagen and gelatin, it has weaker bone induction and bone growth promotion capabilities.

[0003] A Chinese invention patent (CN111956871) discloses a silk protein / gelatin composite material and its use: mulberry silkworm cocoons are immersed in a soap salt solution for degumming and drying to obtain degummed silk, and the degummed silk is then dissolved in a lithium bromide solution, dialyzed for desalination, and concentrated to obtain a silk protein solution; the silk protein solution is mixed with a gelatin solution, horseradish peroxidase, a hydrogen peroxide solution, and a glutamine transaminase are added, and the mixture is mixed to form a gel to obtain a silk protein / gelatin gel; the silk protein / gelatin gel is immersed in alcohol and ammonium sulfate solutions respectively to obtain a silk protein / gelatin cross-linked gel, and the columnar or block-shaped mother embryo is obtained by drying.

[0004] However, the composite material disclosed in the above invention does not have a porous structure and cannot provide a three-dimensional space for the adhesion, proliferation and migration of bone repair cells, which results in inefficient transportation of nutrients and water to cells and affects the osteogenic activity of the material.

[0005] Furthermore, Viviana et al. disclosed a method in J.Actbio.2018.03.047: immersing silkworm cocoons in a soap salt solution for degumming and drying to produce degummed silk, and then dissolving the degummed silk in a lithium bromide solution, desalting by dialysis, and concentrating to produce a silk protein solution; adding horseradish peroxidase and hydrogen peroxide solution to the silk protein solution, and transferring it into a mold before gelation; slowly adding granular sodium chloride to the solution and gelling at 37°C; soaking the silk protein gel in purified water, filtering out the undissolved salt particles, and obtaining a porous gel; taking it out of the mold and freeze-drying it.

[0006] However, the silk protein scaffold material prepared by the above method does not contain gelatin components, so that the biological activity of the silk protein scaffold material in promoting cell adhesion, differentiation and growth is lower than that of the material containing gelatin components, that is, the stability and biological function of this material are not as good as those of the composite material containing gelatin components.

[0007] At present, in view of the problems in the related art that the composite material does not have a porous structure and the silk fibroin scaffold material does not contain gelatin components, etc., no effective solution has been proposed yet. Summary of the Invention

[0008] The purpose of the present invention is to provide a composite bone repair material, a preparation method and an application in view of the deficiencies in the prior art, so as to solve the problems in the related art such as the composite material not having a porous structure, weak mechanical properties, and the silk fibroin scaffold material not containing gelatin components.

[0009] To achieve the above purpose, the technical solution adopted by the present invention is:

[0010] In the first aspect, the present invention provides a preparation method of a composite bone repair material, including:

[0011] Immerse the mulberry silkworm cocoons in a soap-salt solution for degumming and drying to make degummed silk, and then dissolve the degummed silk in a lithium bromide solution, dialyze to desalt, and concentrate to obtain a regenerated silk fibroin solution;

[0012] Mix the regenerated silk fibroin solution with a gelatin solution, and sequentially add an aqueous hydrogen peroxide solution, transglutaminase, and horseradish peroxidase to obtain a gel solution;

[0013] Mechanically shake the gel solution to make the gel solution mixed evenly and form uniformly distributed bubbles in the gel solution, and flow the evenly mixed gelatin solution into a mold for gelation to obtain a silk fibroin / gelatin gel block;

[0014] Immerse the silk fibroin / gelatin gel block in an ammonium sulfate solution for soaking and cleaning to obtain a silk fibroin / gelatin crosslinked gel;

[0015] Freeze-dry the silk fibroin / gelatin crosslinked gel to obtain a silk fibroin / gelatin composite material.

[0016] In some of these embodiments, the regenerated silk fibroin solution obtained by immersing the mulberry silkworm cocoons in a soap-salt solution for degumming and drying to make degummed silk, and then dissolving the degummed silk in a lithium bromide solution, dialyzing to desalt, and concentrating includes:

[0017] Cut the cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution and boil for degumming treatment to obtain silk;

[0018] Wash the silk with deionized water repeatedly and dry to obtain silk fibers;

[0019] Put the silk fibers into a lithium bromide solution for dissolution and filter to obtain a silk fibroin stock solution;

[0020] Dialyze and desalt the silk fibroin stock solution to obtain a silk fibroin solution;

[0021] The silk fibroin solution is subjected to reverse dialysis and concentration using polyethylene glycol to obtain a regenerated silk fibroin solution.

[0022] In some of these embodiments, the concentration of the sodium carbonate - sodium bicarbonate buffer is 0.01M to 0.05M.

[0023] In some of these embodiments, the concentration of the lithium bromide solution is 8 to 10M.

[0024] In some of these embodiments, the molecular weight of the polyethylene glycol is 10,000Da to 30,000Da, and the concentration of the polyethylene glycol is 10% to 20%.

[0025] In some of these embodiments, the concentration of the regenerated silk fibroin solution is 5% to 20%.

[0026] In some of these embodiments, the silk is repeatedly washed with deionized water and dried to obtain silk fibers, and the drying temperature is 35°C to 45°C, and the drying time is 20h to 30h.

[0027] In some of these embodiments, the dialysis molecular weight for dialyzing and desalting the silk fibroin stock solution to obtain a silk fibroin solution is 8,000Da to 14,000Da.

[0028] In some of these embodiments, the concentration of the aqueous hydrogen peroxide solution is 0.1% to 1.0%, and the dose of the aqueous hydrogen peroxide solution is 500 to 1000 μl.

[0029] In some of these embodiments, the dose of the transglutaminase is 10 to 200 μl, and the enzyme activity of the transglutaminase is 10 to 100 U / μl.

[0030] In some of these embodiments, the dose of the horseradish peroxidase is 500 - 1000 μL, and the enzyme activity of the horseradish peroxidase is 600 - 1000 U / μL.

[0031] In some of these embodiments, the size of the silk protein / gelatin gel block is 2 to 4 mm.

[0032] In some of these embodiments, the concentration of the ammonium sulfate solution is 10% to 20%, and the dose of the ammonium sulfate solution is 100 to 200 ml.

[0033] In some of these embodiments, the time for freeze - drying is 2 to 8 days.

[0034] In some of these embodiments, the mechanical shaking of the gel solution to make the gel solution mix evenly and form evenly distributed bubbles in the gel solution, and the laminar flow of the evenly mixed gelatin solution into a mold to gel and obtain silk fibroin / gelatin gel blocks includes:

[0035] Mechanically shake the gel solution to make the gel solution mix evenly and form evenly distributed bubbles in the gel solution, and laminar flow the evenly mixed gelatin solution into a mold to gel;

[0036] After initial gelling, cut the gel to obtain a number of silk fibroin / gelatin gel blocks.

[0037] In some of these embodiments, it includes:

[0038] Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution with a concentration of 0.02 M and boil for degumming treatment to obtain silk;

[0039] Wash the silk repeatedly with deionized water and dry it at 40 °C for 24 h to obtain silk fibers;

[0040] Put the silk fibers into a lithium bromide solution with a concentration of 9 M to dissolve, and filter to obtain a silk fibroin stock solution;

[0041] Dialyze and desalt the silk fibroin stock solution under the condition of a dialysis molecular weight of 10,000 Da to obtain a silk fibroin solution;

[0042] After reverse dialysis and concentration of the silk fibroin solution using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da, a regenerated silk fibroin solution with a concentration of 10% is obtained;

[0043] Mix the regenerated silk fibroin solution with a concentration of 10% and a gelatin solution with a concentration of 30%, and sequentially add an aqueous hydrogen peroxide solution with a concentration of 0.5% and a dose of 700 μl, a transglutaminase with a dose of 100 μl and an enzyme activity of 50 U / μl, and a horseradish peroxidase with a dose of 700 μl and an enzyme activity of 500 U / mL to obtain a gel solution;

[0044] Mechanically shake the gel solution to make the gel solution mix evenly and form evenly distributed bubbles in the gel solution, and laminar flow the evenly mixed gelatin solution into a mold to gel;

[0045] After initial gelling, cut the gel to obtain a number of silk fibroin / gelatin gel blocks with a size of 3 mm;

[0046] Soak and wash the silk fibroin / gelatin gel blocks in a 15% ammonium sulfate solution to obtain silk fibroin / gelatin crosslinked gel;

[0047] The silk fibroin / gelatin crosslinked gel was freeze-dried for 5 days to obtain a silk fibroin / gelatin composite material.

[0048] In a second aspect, the present invention also provides a composite bone repair material prepared by the preparation method described in the first aspect.

[0049] In some of these embodiments, the composite bone repair material is in the shape of regular particles, irregular particles, spherical solids, cylindrical solids, cubic solids, rectangular solids, or irregular-shaped solids.

[0050] The composite bone repair material is provided with a porous structure at the micron or nanometer scale, and the porosity of the composite bone repair material is 20% - 90%.

[0051] The structural strength (compressive strength) of the composite bone repair material is 0.1 - 35 MPa.

[0052] In a third aspect, the present invention also provides an application of a composite bone repair material in the preparation of a bone filling material, which is applied to the filling and regenerative repair of bone defects in orthopedics, oral, plastic surgery, and neurosurgery cranial bones. The composite bone repair material is prepared by the preparation method described in the first aspect or the composite bone repair material described in the second aspect.

[0053] The present invention adopts the above technical solutions. Compared with the prior art, it has the following technical effects:

[0054] 1. The raw materials silk fibroin and gelatin used in the present invention are rich in yield, low in price, and are raw materials for medical products certified by the US Food and Drug Administration. They have good biocompatibility, biological functions, and biodegradability.

[0055] 2. The horseradish peroxidase, hydrogen peroxide, and transglutaminase used in the present invention have all been commercially mass-produced. Among them, transglutaminase is prepared from a microbial source, which has more uniform stability and higher yield compared to the original mammalian source. Low concentrations of horseradish peroxidase and hydrogen peroxide are non-toxic and have good biocompatibility. Experiments and literature have proven that the silk fibroin and gelatin hydrogels crosslinked by horseradish peroxidase and transglutaminase are non-toxic to cells and animals.

[0056] 3. The present invention applies horseradish peroxidase / hydrogen peroxide to induce crosslinking between silk fibroin itself and silk fibroin-gelatin, applies transglutaminase to modify the gelatin side branches, and immerses the obtained hydrogel in a 70% alcohol solution and a 15% ammonium sulfate solution in sequence to further induce the formation of a small and uniform silk fibroin β-sheet in the gel area and strengthen the modification of the gelatin branches, so that the composite material obtains stability in vitro and in animals while having high strength and compressive properties.

[0057] 4. Based on the existing silk protein materials, the present invention has the biological functions of promoting cell adhesion, growth, and differentiation improved by adding gelatin;

[0058] 5. Based on the existing silk protein / gelatin materials, the present invention prepares a porous material, which has the advantages of high porosity and large void ratio, greatly promoting cell growth, such as cell proliferation and migration, and tissue growth, which is very beneficial to the clinical application of tissue engineering technology;

[0059] 6. The composite material prepared by the present invention, which is a bone filling material with a certain porosity, can provide a three-dimensional space for the adhesion, proliferation, and migration of bone repair cells, and nutrients and moisture can also be transported to cells through the pores; moreover, the bone filling material prepared by compounding gelatin and silk protein can enhance the osteogenic activity of the material;

[0060] 7. The preparation method of the present invention is simple and efficient, without waste and pollution throughout the process, with good repeatability, and has the potential value of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is a schematic flow chart (one) of the preparation method of the composite bone repair material according to the embodiment of the present invention;

[0062] Figure 2 is a schematic flow chart (two) of the preparation method of the composite bone repair material according to the embodiment of the present invention;

[0063] Figure 3 is a schematic flow chart (three) of the preparation method of the composite bone repair material according to the embodiment of the present invention.

[0064] Figure 4 is a transmission electron microscope (SEM) morphology diagram (four) of the composite bone repair material according to Embodiment 2 of the present invention.

[0065] Figure 5 is a transmission electron microscope (SEM) image (five) of the composite bone repair material and cell adhesion according to Embodiment 2 of the present invention DETAILED DESCRIPTION OF THE EMBODIMENTS

[0066] The raw materials of the silk fibroin / gelatin composite material provided by the present invention are all natural biological materials. As a natural biological protein material, silk fibroin has characteristics such as good biocompatibility, easy availability, good swelling property, and natural antibacterial property. However, due to the slow degradation rate of the pure silk fibroin material, and compared with other proteins such as collagen and gelatin, due to the lack of bioactive peptide segments, its promotion of the biological functions of cells is relatively weak. And pure gelatin is prone to heat denaturation and water absorption swelling. The present invention utilizes the characteristics that silk fibroin is rich in tyrosine, and gelatin is rich in tyrosine, glutamine, and lysine. Horseradish peroxidase and hydrogen peroxide are applied to oxidize tyrosine therein to form dityrosine cross-links, and microbial transglutaminase is used to form glutamine-lysine isopeptide bonds in gelatin through acyl transfer reaction, and an alcohol solvent is added to induce silk fibroin to form β-sheets, and an ammonium sulfate solution is used to strengthen the side chain modification of gelatin. Multiple strategies are combined to enhance the stability and mechanical properties of the silk fibroin-gelatin composite material and endow it with good biological functions.

[0067] The silk fibroin / gelatin composite bone repair material provided by the present invention is a new type of medical biological polymer material, and porous bone repair materials of various specifications can be prepared through mold adjustment and different freeze-drying processes. In clinical surgery, the bone repair material can not only directly fill the bone defect site, but also be used in combination with the nail plate system to improve the ability of bone healing, and the material can be completely biodegradable without the need for a second operation to remove it.

[0068] In order to evaluate the performance of the silk fibroin / gelatin composite bone repair material, the compressive strength of the material was tested in the examples, and the results showed that the material could well meet the usage requirements of defect filling. In addition, through cell adhesion tests, it was verified that the silk fibroin / gelatin composite bone repair material had good cell compatibility, was beneficial to the adhesion and growth of osteoblasts, and was beneficial to bone healing.

[0069] The following further illustrates the present invention in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and not to limit the scope of the present invention. All other examples obtained by those of ordinary skill in the art based on the examples in the present invention without creative efforts shall fall within the scope of protection of the present invention.

[0070] In the examples of the present invention, if no specific description is made for the experimental operation temperature, the temperature generally refers to room temperature.

[0071] In this article, the addition amounts, contents, and concentrations of various substances are involved. Among them, the percentage content, unless otherwise specified, all refer to the weight percentage content.

[0072] The "solution" involved in this article, unless otherwise specified, all refers to an aqueous solution.

[0073] Example 1

[0074] A schematic embodiment of the present invention, as Figure 1 shown, a preparation method of a composite bone repair material, comprising:

[0075] Step S100: Immerse the mulberry silkworm cocoon in a soap salt solution for degumming, dry it to make degummed silk, and then dissolve the degummed silk in a lithium bromide solution, desalt it by dialysis, and concentrate it to obtain a regenerated silk fibroin solution;

[0076] Step S200: Mix the regenerated silk fibroin solution with a gelatin solution, and sequentially add an aqueous hydrogen peroxide solution, transglutaminase, and horseradish peroxidase to obtain a gel solution;

[0077] Step S300: Mechanically shake the gel solution to make the gel solution mixed evenly and form uniformly distributed bubbles in the gel solution, and flow the evenly mixed gelatin solution into a mold to gel to obtain a silk fibroin / gelatin gel block;

[0078] Step S400: Immerse and wash the silk fibroin / gelatin gel block in an ammonium sulfate solution to obtain a silk fibroin / gelatin crosslinked gel;

[0079] Step S500: Freeze-dry the silk fibroin / gelatin crosslinked gel to obtain a silk fibroin / gelatin composite material.

[0080] It should be noted that in step S200, the concentration of the regenerated silk fibroin solution is 5% - 40%, and the concentration of the gelatin solution is 5% - 40%. Preferably, the concentration of the regenerated silk fibroin solution is 10%, and the concentration of the gelatin solution is 30%.

[0081] It should be noted that in step S200, the concentration of the aqueous hydrogen peroxide solution is 0.1% - 1.0%, and the dosage of the aqueous hydrogen peroxide solution is 500 - 1000 μl. Preferably, the concentration of the aqueous hydrogen peroxide solution is 0.5%, and the dosage of the aqueous hydrogen peroxide solution is 800 μl.

[0082] It should be noted that in step S200, the dosage of transglutaminase is 10 - 200 μl, and the enzyme activity of transglutaminase is 10 - 100 U / μl. Preferably, the dosage of transglutaminase is 100 μl, and the enzyme activity of transglutaminase is 50 U / μl.

[0083] It should be noted that in step S200, the dosage of horseradish peroxidase is 500 - 1000 μL, and the enzyme activity of horseradish peroxidase is 600 - 1000 U / mL. Preferably, the dosage of horseradish peroxidase is 700 μL, and the enzyme activity of horseradish peroxidase is 800 U / mL.

[0084] It should be noted that in step S400, the concentration of the ammonium sulfate solution is 10% - 20%, and the dosage of the ammonium sulfate solution is 100 - 200 ml. Preferably, the concentration of the ammonium sulfate solution is 15%, and the dosage of the ammonium sulfate solution is 150 ml (generally, 100 - 200 ml of ammonium sulfate solution is required for 20 ml of gel).

[0085] It should be noted that in step S500, the freeze-drying time is 2 - 8 days. Preferably, the freeze-drying time is 5 days.

[0086] As Figure 2 shown, step S100 includes:

[0087] Step S110: Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution and boil them for degumming treatment to obtain silk fibers;

[0088] Step S120: Wash the silk fibers repeatedly with deionized water and dry them to obtain silk fibers;

[0089] Step S130: Put the silk fibers into a lithium bromide solution for dissolution and filter to obtain a silk fibroin stock solution;

[0090] Step S140: Dialyze and desalt the silk fibroin stock solution to obtain a silk fibroin solution;

[0091] Step S150: After reverse dialysis and concentration of the silk fibroin solution using polyethylene glycol, a regenerated silk fibroin solution is obtained.

[0092] It should be noted that in step S110, the concentration of the sodium carbonate-sodium bicarbonate buffer solution is 0.01M - 0.05M. Preferably, the concentration of the sodium carbonate-sodium bicarbonate buffer solution is 0.02M.

[0093] It should be noted that in step S120, the drying temperature is 35°C - 45°C and the drying time is 20h - 30h. Preferably, the drying temperature is 340°C and the drying time is 24h.

[0094] It should be noted that in step S130, the concentration of the lithium bromide solution is 8 - 10M. Preferably, the concentration of the lithium bromide solution is 9M.

[0095] It should be noted that in step S140, the dialysis molecular weight is 8,000 Da - 14,000 Da. Preferably, the dialysis molecular weight is 10,000 Da.

[0096] It should be noted that in step S150, the molecular weight of the polyethylene glycol is 10,000 Da - 30,000 Da, and the concentration of the polyethylene glycol is 10% - 20%. Preferably, the molecular weight of the polyethylene glycol is 20,000 Da and the concentration of the polyethylene glycol is 15%.

[0097] It should be noted that the concentration of the regenerated silk fibroin solution in step S150 is 5% to 20%. Preferably, the concentration of the regenerated silk fibroin solution is 10%.

[0098] As Figure 3 shown, step S300 includes:

[0099] Step S310: Mechanically shake the gel solution to make the gel solution evenly mixed and form evenly distributed bubbles in the gel solution, and flow the evenly mixed gelatin solution into the mold for gelation;

[0100] Step S320: Cut the gel after preliminary gelation to obtain several silk fibroin / gelatin gel blocks.

[0101] It should be noted that the mechanical shaking measure in step S310 can be carried out by means of vortex at different speeds, repeated rotation, magnetic stirrer, paddle stirring, etc.

[0102] It should be noted that the size of the silk fibroin / gelatin gel block in step S310 is 2 to 4 mm 3 . Preferably, the size of the silk fibroin / gelatin gel block is 3 mm 3 .

[0103] It should be noted that the shape of the composite bone repair material is set as regular particles, irregular particles, spherical solids, cylindrical solids, cubic solids, rectangular solids, and irregularly shaped solids.

[0104] It should be noted that the composite bone repair material is set with a porous structure at the micron or nanometer scale, and the porosity of the composite bone repair material is 20% to 90%.

[0105] It should be noted that the structural strength (compressive strength) of the composite bone repair material is 0.1 to 35 MPa.

[0106] It should be noted that the composite bone repair material is applied in the preparation of bone filling materials, and is used for the filling and regenerative repair of bone defects in orthopedics, stomatology, plastic surgery, and neurosurgery cranial bones.

[0107] The present invention has the following advantages:

[0108] 1. The raw materials silk fibroin and gelatin used in the present invention are rich in output, low in price, and are raw materials for medical products certified by the US Food and Drug Administration, and have good biocompatibility, biological functions, and biodegradability;

[0109] 2. The horseradish peroxidase, hydrogen peroxide, and transglutaminase used in the present invention have all been commercially mass-produced. Among them, transglutaminase is prepared from a microbial source, which has more uniform stability and higher yield compared to the original mammalian source. Low concentrations of horseradish peroxidase and hydrogen peroxide are non-toxic and have good biocompatibility. Experiments and literature have proven that the silk fibroin and gelatin hydrogels crosslinked by horseradish peroxidase and transglutaminase are non-toxic to cells and animals;

[0110] 3. The present invention applies horseradish peroxidase / hydrogen peroxide to induce the crosslinking of silk fibroin itself and between silk fibroin and gelatin, and uses transglutaminase to modify the gelatin side chains. The obtained hydrogel is successively soaked in a 70% alcohol solution and a 15% ammonium sulfate solution to further induce the formation of small and uniform silk fibroin β-sheets and strengthen the modification of gelatin side chains, enabling the composite material to obtain stability both in vitro and in vivo while possessing high strength and compressive properties;

[0111] 4. Based on the existing silk fibroin materials, the present invention has improved biological functions of promoting cell adhesion, growth, and differentiation by adding gelatin;

[0112] 5. Based on the existing silk fibroin / gelatin materials, the present invention prepares a porous material with the advantages of high porosity and large voids, which greatly promotes cell growth, such as cell proliferation and migration, and tissue growth, and is very beneficial for the clinical application of tissue engineering technology;

[0113] 6. The composite material with a certain porosity prepared in the present invention can provide a three-dimensional space for the adhesion, proliferation, and migration of bone repair cells, and nutrients and moisture can also be transported to cells through the pores; moreover, the bone filling material prepared by compounding gelatin and silk fibroin can enhance the osteogenic activity of the material;

[0114] 7. The preparation method of the present invention is simple, efficient, waste-free and pollution-free throughout the process, has good repeatability, and has the potential value for industrial production.

[0115] Example 2

[0116] This example relates to a specific implementation method of the preparation method of the composite bone repair material.

[0117] A preparation method of a composite bone repair material, comprising:

[0118] Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution with a concentration of 0.02M, and boil them for degumming treatment to obtain silk;

[0119] Wash the silk repeatedly with deionized water and dry it at 40°C for 24 h to obtain silk fibers;

[0120] Put the silk fiber into a lithium bromide solution with a concentration of 9M for dissolution, and filter to obtain the silk fibroin stock solution;

[0121] Dialyze and desalt the silk fibroin stock solution under the condition of 10,000Da to obtain the silk fibroin solution;

[0122] Reverse dialyze and concentrate the silk fibroin solution with polyethylene glycol with a concentration of 15% and a molecular weight of 20,000Da to obtain a 10% regenerated silk fibroin solution;

[0123] Uniformly mix the 10% regenerated silk fibroin solution and the 30% gelatin solution in a ratio of 85:15, and sequentially add an aqueous hydrogen peroxide solution with a concentration of 0.5% and a dose of 800μl, a transglutaminase with a dose of 100μl and an enzyme activity of 50U / μl, and a horseradish peroxidase with a dose of 700μl and an enzyme activity of 500U / mL to obtain a gel solution;

[0124] Mechanically shake the gel solution to make the gel solution uniformly mixed and form uniformly distributed bubbles in the gel solution, and flow the uniformly mixed gelatin solution into the mold for gelation;

[0125] After preliminary gelation, cut the gel to obtain a number of silk protein / gelatin gel blocks with a size of 3mm 3 ;

[0126] Soak and wash the silk protein / gelatin gel blocks in a 15% ammonium sulfate solution to obtain silk protein / gelatin crosslinked gel;

[0127] Freeze-dry the silk protein / gelatin crosslinked gel for 5 days to obtain the silk protein / gelatin composite material.

[0128] The advantages of this example are the same as those of Example 1 and will not be elaborated here.

[0129] Example 3

[0130] This example relates to another specific implementation of the preparation method of the composite bone repair material.

[0131] A preparation method of a composite bone repair material, comprising:

[0132] Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution with a concentration of 0.02M and boil for degumming treatment to obtain silk;

[0133] Wash the silk repeatedly with deionized water and dry it at 40°C for 24h to obtain silk fibers;

[0134] Put the silk fibers into a lithium bromide solution with a concentration of 9M for dissolution, and filter to obtain the silk fibroin stock solution;

[0135] Dialyze and desalt the silk fibroin stock solution under the condition of 10,000 Da to obtain a silk fibroin solution;

[0136] Reverse dialyze and concentrate the silk fibroin solution with polyethylene glycol having a concentration of 15% and a molecular weight of 20,000 Da to obtain a 10% regenerated silk fibroin solution;

[0137] Mix the 10% regenerated silk fibroin solution and the 30% gelatin solution at a ratio of 60:40, and sequentially add an aqueous hydrogen peroxide solution with a concentration of 0.5% and a dose of 800 μl, transglutaminase with a dose of 100 μl and an enzyme activity of 50 U / μl, and horseradish peroxidase with a dose of 700 μl and an enzyme activity of 500 U / mL to obtain a gel solution;

[0138] Mechanically shake the gel solution to make the gel solution uniformly mixed and form uniformly distributed bubbles in the gel solution, and flow the uniformly mixed gelatin solution into a mold for gelling;

[0139] After preliminary gelling, cut the gel to obtain a number of silk protein / gelatin gel blocks with a size of 3 mm 3 ;

[0140] Soak and wash the silk protein / gelatin gel blocks in a 15% ammonium sulfate solution to obtain silk protein / gelatin crosslinked gel;

[0141] Lyophilize the silk protein / gelatin crosslinked gel for 5 days to obtain a silk protein / gelatin composite material.

[0142] The advantages of this example are the same as those of Example 1 and will not be elaborated here.

[0143] Example 4

[0144] This example relates to another specific implementation manner of the preparation method of the composite bone repair material.

[0145] A preparation method of a composite bone repair material, comprising:

[0146] Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution with a concentration of 0.02 M and boil for degumming treatment to obtain silk;

[0147] Wash the silk repeatedly with deionized water and dry it at 40 °C for 24 h to obtain silk fibers;

[0148] Put the silk fibers into a lithium bromide solution with a concentration of 9 M for dissolution and filter to obtain a silk fibroin stock solution;

[0149] Dialyze and desalt the silk fibroin stock solution under the condition of 10000 Da to obtain a silk fibroin solution;

[0150] The silk fibroin solution was subjected to reverse dialysis and concentration using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a regenerated silk fibroin solution with a concentration of 10%.

[0151] The 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution at a ratio of 85:15, and an aqueous hydrogen peroxide solution with a concentration of 0.5% and a dose of 800 μl, transglutaminase with a dose of 100 μl and an enzyme activity of 50 U / μl, and horseradish peroxidase with a dose of 700 μl and an enzyme activity of 500 U / mL were sequentially added to obtain a gel solution.

[0152] The gel solution was mechanically shaken to make the gel solution mixed evenly and form uniformly distributed bubbles in the gel solution, and the evenly mixed gelatin solution was flowed into a mold to gel.

[0153] After preliminary gelling, the gel was cut to obtain a number of silk protein / gelatin gel blocks with a size of 3 mm 3 .

[0154] The gel blocks were immersed and washed in an ethanol solution with a concentration of 75% to obtain silk protein / gelatin crosslinked gel.

[0155] The silk protein / gelatin gel blocks were immersed and washed in a 15% ammonium sulfate solution to obtain silk protein / gelatin crosslinked gel.

[0156] The silk protein / gelatin crosslinked gel was freeze-dried for 5 days to obtain a silk protein / gelatin composite material.

[0157] The advantages of this example are the same as those of Example 1 and will not be elaborated here.

[0158] Example 5

[0159] This example relates to another specific implementation of the preparation method of the composite bone repair material.

[0160] A preparation method of a composite bone repair material, comprising:[[]]

[0161] The silkworm cocoons were cut into pieces and put into a sodium carbonate-sodium bicarbonate buffer solution with a concentration of 0.02 M and boiled for degumming treatment to obtain silk.

[0162] The silk was repeatedly washed with deionized water and dried at 40 °C for 24 h to obtain silk fibers.

[0163] The silk fibers were put into a lithium bromide solution with a concentration of 9 M to dissolve and filtered to obtain a silk fibroin stock solution.

[0164] The silk fibroin stock solution was dialyzed and desalted under the condition of 10,000 Da to obtain a silk fibroin solution;

[0165] The silk fibroin solution was subjected to reverse dialysis and concentration using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000 Da to obtain a 10% regenerated silk fibroin solution;

[0166] The 10% regenerated silk fibroin solution was mixed with a 30% gelatin solution at a ratio of 85:15, and an aqueous hydrogen peroxide solution with a concentration of 0.5% and a dose of 800 μl, transglutaminase with a dose of 100 μl and an enzyme activity of 50 U / μl, and horseradish peroxidase with a dose of 700 μl and an enzyme activity of 500 U / mL were successively added to obtain a gel solution;

[0167] The solution was flowed into a mold for gelation;

[0168] After preliminary gelation, the gel was cut to obtain a number of silk protein / gelatin gel blocks with a size of 3 mm 3 ;

[0169] The silk protein / gelatin gel blocks were immersed and washed in a 15% ammonium sulfate solution to obtain silk protein / gelatin crosslinked gels;

[0170] The silk protein / gelatin crosslinked gels were freeze-dried for 5 days to obtain silk protein / gelatin composite materials.

[0171] The advantages of this example are the same as those of Example 1 and will not be elaborated here.

[0172] Example 6

[0173] This example relates to the porosity and pore size testing of composite bone repair materials

[0174] For the silk protein / gelatin composite bone repair materials obtained in Examples 2-5, the porosity and pore size distribution were tested according to the following method.

[0175] According to the recommended standard ISO 15901-1:2005 of the International Organization for Standardization (ISO), a mercury intrusion porosimeter, a dilatometer and liquid mercury for measurement were used to test the porosity and pore size distribution of the bone repair materials obtained in different examples. Several samples of about 3-5 mm 3 were weighed and the data were recorded; then, the samples were placed in a dry and clean sample dilatometer, and the samples were evacuated to remove water vapor and other gases to keep the samples in a vacuum state; finally, mercury was injected into the sample dilatometer with a filling pressure less than 5 kPa; during the pressure increase process, the external pressure and the mercury injection volume were recorded using a chart or a computer; after the test was completed, a chart was drawn based on the recorded values to obtain the pore size distribution and porosity.

[0176] The experimental results are shown in Table 1. The porosity of the composite bone repair materials obtained by the preparation methods described in Example 2, Example 3, and Example 5 is greater than 50% and less than 75%; the pore size ranges from 1 nm to 500 μm; among them, the pore size distribution of the composite bone repair material obtained by the preparation method described in Example 2 is relatively narrow, within the range of 1 μm to 200 μm. Among them, the micro scanning electron microscope (SEM) photograph of the composite bone repair material obtained by the preparation method described in Example 2 is as Figure 4 shown.

[0177] Example 7

[0178] This example relates to the compressive strength test of the composite bone repair material

[0179] For the silk fibroin / gelatin composite bone repair materials obtained in Examples 2-5, the anti-compressive mechanical strength was tested according to the following method.

[0180] According to the recommended standard ISO13175-3:2012 of the International Organization for Standardization (ISO), a universal mechanical tester Instron 3366 (Instron, USA), a 10 kN load cell, a customized metal base for pressure testing, and a pressure block (hardness 300 HV or higher) were used to perform compression tests on the bone repair materials obtained in different examples. The samples were pre-processed into cuboid samples of 10×10×15 mm and fixed at the center of the metal base; the metal pressure block was loaded on the universal mechanical tester, directly above the sample block; the downward pressing rate was set at 0.5 mm / min, and the sample block was compressed until it was damaged. The maximum load was recorded and the compressive strength (unit: MPa) was calculated.

[0181] The experimental results are shown in Table 1. The compressive strengths of Examples 2, 4, and 5 are all greater than 2.0 MPa, and in particular, Example 4 can reach 3.6±0.5 MPa. Combining with the test results of Example 6, it can be seen that bone repair materials with different porosities, pore size distributions, and compressive mechanical properties can be prepared by the preparation method of this case. It has potential clinical application prospects and values.

[0182] Group Porosity Pore size (μm) Compressive strength (MPa) Example 2 70%~75% 1~200 2.4±0.5 Example 3 50%~70% 0.6~50 1.8±0.6 Example 4 35%~40% 0.010~10 3.6±0.5 Example 5 50%~60% 0.200~40 2.5±0.3

[0183] Table 1. Comparison of different samples of bone repair materials

[0184] Example 8

[0185] This example relates to the cytocompatibility test of the composite bone repair material

[0186] For the silk fibroin / gelatin composite bone repair material obtained in Example 2, the cell adhesion was tested according to the following method.

[0187] To evaluate the cell adhesion of the bone repair material, bone marrow mesenchymal stem cells (BMSCs) were seeded onto the bone repair material at a density of 1×104 cells / mL and co-cultured for 3 days. Then the samples were rinsed with phosphate buffer solution (PBS) to remove non-adherent cells, fixed with glutaraldehyde at 4°C, and dehydrated through a gradient ethanol solution. Subsequently, the samples were dried in a forced-air drying oven at 40°C for 2 days. The microscopic scanning electron microscopy (SEM) photographs of the cell adhesion on the surface of the composite bone repair material obtained by the preparation method described in Example 2 and their enlarged pictures are as shown in Figure 5 shown.

[0188] It can be seen from the pictures that the cells have successfully adhered to the surface of the material, and some cells have entered the pores on the surface. The morphology is spread out with obvious pseudopodia and they are connected to each other (as shown by the arrows), indicating that the silk fibroin / gelatin composite bone repair material prepared by this preparation method has good cell compatibility and is conducive to cell adhesion, proliferation and migration.

[0189] The technical features of the above-described embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope described in this specification.

[0190] The above-described embodiments only represent several implementation manners of the present application. The description is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several modifications and improvements can still be made, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the appended claims.

Claims

1. A preparation method of a composite bone repair material, characterized in that Including: Immerse the silkworm cocoons in a soap-salt solution for degumming, then dry them to obtain degummed silk. The degummed silk is then dissolved in a lithium bromide solution, dialyzed to remove salt, and concentrated to obtain a regenerated silk protein solution; Mix the regenerated silk fibroin protein solution with a gelatin solution, and successively add an aqueous hydrogen peroxide solution, transglutaminase, and horseradish peroxidase to obtain a gel solution; Mechanically shake the gel solution to make it uniformly mixed and form uniformly distributed bubbles in the gel solution. Then, flow the uniformly mixed gelatin solution into a mold to gel and obtain a silk protein / gelatin gel block; Immerse the silk protein / gelatin gel block in an ammonium sulfate solution, soak and wash it to obtain a silk protein / gelatin crosslinked gel; Freeze-dry the silk protein / gelatin crosslinked gel to obtain a silk protein / gelatin composite material.

2. The preparation method according to claim 1, characterized in that, The regenerated silk protein solution obtained by immersing the mulberry silkworm cocoons in a soap-salt solution for degumming, drying, dissolving in a lithium bromide solution, dialyzing to remove salt, and concentrating includes: Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution and boil for degumming treatment to obtain silk; Wash the silk repeatedly with deionized water and dry it to obtain silk fibers; Put the silk fibers into a lithium bromide solution to dissolve and filter to obtain a silk fibroin stock solution; Dialyze and desalt the silk fibroin stock solution to obtain a silk fibroin solution; After reverse dialysis and concentration of the silk fibroin solution using polyethylene glycol, a regenerated silk fibroin solution is obtained.

3. The preparation method according to claim 2, wherein The concentration of the sodium carbonate-sodium bicarbonate buffer solution is 0.01M - 0.05M; and / or The concentration of the lithium bromide solution is 8 - 10M; and / or The molecular weight of the polyethylene glycol is 10000Da - 30000Da, and the concentration of the polyethylene glycol is 10% - 20%; and / or The concentration of the regenerated silk fibroin solution is 5% - 20%.

4. The preparation method according to claim 2, characterized in that, The drying temperature in drying the silk with deionized water repeatedly washed and dried to obtain silk fibers is 35°C - 45°C, and the drying time is 20h - 30h; and / or The dialysis molecular weight in dialyzing and desalting the silk fibroin stock solution to obtain a silk fibroin solution is 8000Da - 14000Da.

5. The preparation method according to claim 1, characterized in that, The concentration of the aqueous hydrogen peroxide solution is 0.1% - 1.0%, and the dosage of the aqueous hydrogen peroxide solution is 500 - 1000μl; The dosage of the transglutaminase is 10 - 200μl, and the enzyme activity of the transglutaminase is 10 - 100U / μl; The dosage of the horseradish peroxidase is 500 - 1000μL, and the enzyme activity of the horseradish peroxidase is 600 - 1000U / mL; and / or The size of the silk protein / gelatin gel block is 2 - 4mm; and / or The concentration of the ammonium sulfate solution is 10% - 20%, and the dosage of the ammonium sulfate solution is 100 - 200ml; and / or The freeze-drying time is 2 - 8 days.

6. The preparation method according to claim 1, characterized in that, The step of mechanically shaking the gel solution to make it uniformly mixed and form uniformly distributed bubbles in the gel solution, flowing the uniformly mixed gelatin solution into a mold to gel, and obtaining a silk protein / gelatin gel block includes: Mechanically shake the gel solution to make the gel solution evenly mixed and form evenly distributed bubbles in the gel solution, and flow the evenly mixed gelatin solution into the mold for gelation; After preliminary gelation, cut the material to obtain several fibroin / gelatin gel blocks.

7. The preparation method according to any one of claims 1 to 6, characterized in that, Including: Cut the silkworm cocoons into pieces, put them into a sodium carbonate-sodium bicarbonate buffer solution with a concentration of 0.02M and boil for degumming treatment to obtain silk; Wash the silk repeatedly with deionized water and dry it at 40°C for 24h to obtain silk fibers; Put the silk fibers into a lithium bromide solution with a concentration of 9M for dissolution and filter to obtain a fibroin stock solution; Dialyze and desalt the fibroin stock solution under the condition of 10,000Da to obtain a fibroin solution; After reverse dialysis and concentration of the fibroin solution using polyethylene glycol with a concentration of 15% and a molecular weight of 20,000Da, a regenerated fibroin solution with a concentration of 10% is obtained; Mix the regenerated fibroin solution with a concentration of 10% and a gelatin solution with a concentration of 30%, and sequentially add an aqueous hydrogen peroxide solution with a concentration of 0.5% and a dose of 700μl, a transglutaminase with a dose of 100μl and an enzyme activity of 50U / μl, and a horseradish peroxidase with a dose of 700μl and an enzyme activity of 500U / mL to obtain a gel solution; Mechanically shake the gel solution to make the gel solution evenly mixed and form evenly distributed bubbles in the gel solution, and flow the evenly mixed gelatin solution into the mold for gelation; After preliminary gelation, cut the gel to obtain several fibroin / gelatin gel blocks with a size of 3mm; Soak and wash the fibroin / gelatin gel blocks in a 15% ammonium sulfate solution to obtain fibroin / gelatin crosslinked gel; Freeze-dry the fibroin / gelatin crosslinked gel for 5 days to obtain a fibroin / gelatin composite material.

8. A composite bone repair material, characterized in that, Prepared by the preparation method described in any one of claims 1 to 7.

9. The composite bone repair material according to claim 8, characterized in that The shape of the composite bone repair material is set as regular particles, irregular particles, spherical solids, cylindrical solids, cubic solids, rectangular solids, and irregular-shaped solids; The composite bone repair material is provided with a porous structure at the micron or nanoscale, and the porosity of the composite bone repair material is 20% to 90%; The structural strength (compressive strength) of the composite bone repair material is 0.1 to 35MPa.

10. Use of a composite bone repair material in the preparation of a bone filling material, applied to the filling and regenerative repair of bone defects in orthopedics, dentistry, plastic surgery (maxillofacial), and neurosurgery cranial bones, characterized in that, The composite bone repair material is prepared by the preparation method described in any one of claims 1 to 7 or the composite bone repair material described in any one of claims 8 to 9.

Citation Information

Cited By

  • Regenerated silk fibroin material, and preparation method therefor and use thereof

    WO2026057053A1